Research on the Relationship between ESG Performance and Performance of Listed Companies under the Dual Carbon Target-the Mediating Effect Model Based on Internal Control - Quan, Jiahui; Zhou, Zejiong (International Journal of Global Economics and Management, 2024)
Under the guidance of the dual-carbon goal, the relationship between corporate environmental, social and governance (ESG) performance and performance has received increasing attention. This study uses internal control as an intermediary variable to analyze the interaction mechanism between ESG performance and corporate performance. This paper selects the data of Shanghai and Shenzhen listed companies in the past ten years for analysis, and uses multiple regression models, intermediary effect models and other methods to empirically test the direct impact of ESG performance on corporate performance and the indirect impact through internal control. The research finds that good ESG performance can promote the improvement of corporate performance, and good internal control can strengthen corporate governance, and then effectively regulate ESG performance and corporate performance, thus indirectly promoting the improvement of financial performance. This study proves the importance and necessity of optimizing enterprise ESG performance and strengthening enterprise internal control to promote high-quality sustainable development of enterprises in the context of dual-carbon. This study provides a theoretical basis and practical guidance for enterprises to achieve a win-win situation of economic benefits and social responsibility while pursuing sustainable development.